2021
DOI: 10.25259/apos_158_2020
|View full text |Cite
|
Sign up to set email alerts
|

The role of impacted third molar angulation on the anterior crowding

Abstract: Objectives: The aim of this study was to assess the role of impacted third molar angulation on the severity of anterior crowding. Materials and Methods: Panoramic radiographs and three-dimensional (3D) digital models of 45 patients satisfying the following inclusion criteria were selected for this study. To calculate the irregularity index of Little, the sum of the contact point displacements from the anatomical contact point to the contact point among the lower canine teeth was measured on 3D digital models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The results confirmed that there was no significant association between the angulation pattern of IM3M and the severity of MAC. Similar studies have supported this finding, with a study conducted by Gökçe, G. et al in 2021 demonstrating no correlation between IM3M and MAC ( Gökçe et al, 2021 ). Another study evaluated the influence of IM3M on the relapse of MAC in orthodontically treated patients and reached the conclusion that the presence or absence of mandibular third molars does not affect the relapse of MAC ( Cotrin et al, 2020 ).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results confirmed that there was no significant association between the angulation pattern of IM3M and the severity of MAC. Similar studies have supported this finding, with a study conducted by Gökçe, G. et al in 2021 demonstrating no correlation between IM3M and MAC ( Gökçe et al, 2021 ). Another study evaluated the influence of IM3M on the relapse of MAC in orthodontically treated patients and reached the conclusion that the presence or absence of mandibular third molars does not affect the relapse of MAC ( Cotrin et al, 2020 ).…”
Section: Discussionsupporting
confidence: 78%
“…The role of IM3M in exerting forces that can lead to MAC has been a controversial subject among dentists from various dental specialties, particularly oral surgeons and orthodontists, for numerous years ( Alnamlah et al, 2021 , Gökçe et al, 2021 ). A study conducted in Saudi Arabia aimed to compare the perspectives of Saudi oral surgeons and orthodontists regarding the prophylactic extraction of IM3M to prevent MAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In contrast, other authors could not find any evidence supporting this idea. [18][19][20][21] Furthermore, in the cases of anterior crowding, extracting the third molars did not alleviate the problem, and third molar extraction is not necessary to prevent crowding. 19,20 Harris 22 advocated that the main reason for late anterior crowding is masticatory forces, not eruption of the third molars.…”
Section: Discussionmentioning
confidence: 99%